Clinico-pathological and ultrasonographic observations in canine hepatopathies - VARSHNEY, J P; HOQUE, M (The Indian Journal of Animal Sciences, 2014)
Findings of ultrasonography were analyzed in 24 dogs with hepatopathies and in 3 dogs without hepatopathy and compared with the results of haemato-biochemical investigations. Ultrasonographic appearance of liver demonstrated diffuse hyperechoic "bright" but small liver in cirrhosis and in intrahepatic porto-systemic shunt (PSS); and diffuse fine hypoechoic hepatic changes with hepatomegaly in chronic active hepatitis. Mostly a single shunt either between intmhepatic vena cava and portal vein (most common) or intrahepatic portal and hepatic vasculature was detected sonographically, confirming the diagnosis of intrahepatic PSS. Predominance of target cells, poikilocytes, microcytes, crystals of ammonium biurate in urine was constant finding in PSS. Serum protein, serum albumin, BUN, blood glucose, SAP, ALT were on lower side in PSS. However, SAP, ALT and arginase values were high in chronic active hepatitis.